Open Globe Injury with Corneal Laceration Full-Thickness, Anterior Lens Capsule Rupture, and Traumatic Cataract - Rahadi Akbar; Budy Surakhman; Damaryati Widyastuti (Universitas Airlangga, 2023)
Introduction: Ocular trauma is a common, preventable cause of visual impairment. Mechanical eye injuries affect the eye in many ways ranging from mild to severe morbidity. In this case, we inform the sequence of what we found in this ocular trauma and how we treat this case. Case Presentation: A 26-year-old male patient presented with pain and stiffness in the right eye. The patient was involved in an accident 16 hours before being admitted to the emergency room. Previously, the patient had been taken to a secondary hospital. No medications were given. The patient was referred directly to a tertiary hospital for further management. The visual acuity of the right eye and left eye were 1/300 and 6/6. Soft palpation indicated decreased intraocular pressure (IOP) on the right eye. Slit lamp examination found conjunctival hyperemia, full-thickness corneal laceration, irregular iris, posterior synechiae, declining pupil reflex, and hazy lens. Fundus reflex declined. The right eyeball exploration showed a membrane at the camera oculi anterior and a suspected hazy lens with mass and capsule of the lens. Doubtful prognosis on the right eyeball. Conclusions: The outcome of ocular trauma might be debatable and vary in any condition. Proper management can avoid unprecedented complications and improve patient visual results. A good perspective will also make satisfied both the patient and the physician.